Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1039/c1md00140j
|View full text |Cite
|
Sign up to set email alerts
|

Optimized glucuronidation of dual pharmacology β-2 agonists/M3 antagonists for the treatment of COPD

Abstract: Inhalation by design' concepts were developed to create novel dual pharmacology b-2 agonists-M3 antagonists, for the treatment of chronic obstructive pulmonary disorder. A key feature of this work is the combination of balanced potency and pharmacological duration with optimised glucuronidation through the incorporation of metabolically vulnerable phenols.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…In terms of binding affinity toward the M 3 subtype and selectivity for the M 3 over the M 2 receptor, the biphenyl carbamates OFH244 ( 13m ), OFH243 ( 13n ), OFH3912 ( 14m ), and OFH3911 ( 14n ) range among the best ligands ever developed for this particular muscarinic receptor subtype. In this context, it is interesting to note that 3′-chloro substitution on the B ring already appeared in earlier studies but this effect was so far mainly exploited for the development of highly potent M 1 receptor agonists and nonselective muscarinic antagonists. , As briefly mentioned above, the comparably high affinities of OFH3912 ( 14m ) and OFH3911 ( 14n ) to the M 1 subtype, which is predominantly located in the CNS, postganglionic nerves, and exocrine glands, are less problematic for the quaternary ammonium salts 14m and 14n , as these compounds are unable to pass the blood–brain barrier. For the amines OFH243 ( 13n ) and OFH244 ( 13m ), in contrast, brain penetration can basically not be excluded.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…In terms of binding affinity toward the M 3 subtype and selectivity for the M 3 over the M 2 receptor, the biphenyl carbamates OFH244 ( 13m ), OFH243 ( 13n ), OFH3912 ( 14m ), and OFH3911 ( 14n ) range among the best ligands ever developed for this particular muscarinic receptor subtype. In this context, it is interesting to note that 3′-chloro substitution on the B ring already appeared in earlier studies but this effect was so far mainly exploited for the development of highly potent M 1 receptor agonists and nonselective muscarinic antagonists. , As briefly mentioned above, the comparably high affinities of OFH3912 ( 14m ) and OFH3911 ( 14n ) to the M 1 subtype, which is predominantly located in the CNS, postganglionic nerves, and exocrine glands, are less problematic for the quaternary ammonium salts 14m and 14n , as these compounds are unable to pass the blood–brain barrier. For the amines OFH243 ( 13n ) and OFH244 ( 13m ), in contrast, brain penetration can basically not be excluded.…”
Section: Resultsmentioning
confidence: 95%
“…Having shown that the Phe181/Leu225 distinction between the M 2 and M 3 receptor subtypes represents an eligible starting point for the optimization of M 3 subtype-selective ligands, we continued our research on the lipophilic aromatic moieties pointing at the critical amino acids in ECL2 thereby particularly focusing on nonheterocyclic biphenyl carbamates. The biphenyl motif already was the focus of previous studies and patents; however, none of those focused on a more detailed exploration of substituent effects on the ring systems A and B of the biphenyl moiety (Figure ). Biphenyl carbamates such as 4a and 4b were, for example, studied by Naito, and the pharmacophoric moiety was also incorporated into bivalent ligands , addressing muscarinic and adrenergic receptors.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation